H syndrome - A case report - Patrick Yesudian; K N Sarveswari; K J Karrunya; Kuruvilla Thomas (Wolters Kluwer Medknow Publications, 2019)
This case report describes a case of H syndrome with characteristic cutaneous hyperpigmentation, hypertrichosis, sclerodermatous thickening, and multisystem involvement such as hearing loss and heart anomaly in an Indian patient. There are around 100 cases of this rare, autosomal recessive genodermatosis reported in the literature, out of which 10 cases are from the Indian population. The aim of this paper is to increase awareness about this novel inherited form of histiocytosis and insist on the role of dermatologists to identify such patients in our population where consanguinity is prevalent.